Aplicación de Teorías de Color en Imágenes Digitales - Vega Uribe, Jesús Antonio; Reyes Figueroa, Marlon Alfonso; Restrepo Palacios, ALfredo (Ingeniería, 2004)
Recent works with colour spaces in digital imagen processing are related to colour image segmentation, texture analysis, image morphology, colour image standardization, and object localization. Non-linear systems are frequently present in non-traditional colour spaces (Hering Space) since they help to enhance some specific image characteristics. The present work is related with the study and application of two colour theories: Opponent Colours and Tricromaticity (RGB) as tridimensional representations, using linear and non-linear transformations among these colour spaces. In addition, this paper presents two numeric solutions to solve the implicit non-linear equation system. Due to the positive results obtained with the proposed algorithms, they were implemented to develop a computerized license plate identification system with the introduction of illumination effects.